THE USE OF THE MIND MAPPING METHOD IN SOCIAL SCIENCE LEARNING ON FIFTH GRADES IN THE 13TH ELEMENTARY SCHOOL OF BUNGKU - _, Tahir; _, Misnah; Ratu, Bau; _, Juraid; _, Iskandar; Elfira, Ninil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
This research is motivated by conventional learning methods in the form of lectures which only involve the right hemisphere of the brain. Thus, teachers need to use other learning methods or models in the learning process so that they are expected to be able to involve both hemispheres of the brain in the hope that students can remember information much more easily and learning becomes more active and enjoyable. This research aims to improve student learning outcomes by using mind mapping in social studies learning. This research is classified as qualitative descriptive research, namely explaining how the mind mapping method is implemented in learning social studies for class V students at Bungku 13 State Elementary School. The results of this research explain that the mind mapping method was carried out in 2 stages, namely; planning, implementation. The application of this mind mapping method is able to involve two functions of the human brain in the learning process, namely the right brain and left brain, so it is hoped that it can improve student learning outcomes in social studies learning.